The submental island flap in head and neck reconstruction: A 10‐year experience examining application, oncologic safety, and role of comorbidity - Joseph A. Paydarfar; Peter W. Kahng; Marc A. Polacco; Wenyan Zhao (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Background We present our experience on reconstructive versatility and risk of nodal transfer with the submental island flap (SIF). We also examine the role of comorbidity as a predictor of complications. Methods Retrospective cohort study of patients undergoing SIF over 10‐year period. Comorbidity determined using Adult Comorbidity Evaluation 27 index (ACE‐27). Univariable/multivariable logistic regressions performed to determine association of these characteristics and rates of major complications. Results Fifty‐eight patients underwent SIF reconstruction, 27 (45%) patients had moderate/severe comorbidity, and 24 (41%) experienced major complication. Multivariable analysis identified ACE‐27 scores >2 predictive of major flap complications (OR: 17.38, 95% CI: 1.96–153.74, p = .01) and medical complications (OR: 5.8, 95% CI: 1.11–30.23, p = .037). There were no cases of pathologic nodal transfer. Conclusion The SIF is a versatile flap and oncologically safe in carefully selected patients. The ACE‐27 index is strongly predictive of major postoperative complications. Level of Evidence 4